ANALISIS KESULITAN MEMBACA PEMAHAMAN PADA TEKS DONGENG KELAS V SDN KEDUNG PENGAWAS 02 - Sonia Faradhilla Soraya; Hafizah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the reading comprehension difficulties of fifth grade students at SDN Kedung Pelayan 02, Bekasi. This study uses a qualitative approach with a case study method. The subjects of the study were 33 students, with 5 students having difficulty in achieving the Minimum Completion Criteria (KKM) of 65. Data collection techniques were carried out through observation, interviews, and tests in the form of questions designed to measure students' reading comprehension skills of fairy tale texts. The results of the study showed that the five students had difficulties in five main indicators, namely: (1) difficulty in understanding intrinsic elements in fairy tale texts, (2) difficulty in understanding the meaning of difficult words, (3) difficulty in determining the main idea of the story, (4) difficulty in retelling the contents of the story, and (5) difficulty in determining conclusions from the contents of the story. These difficulties are influenced by several factors including: limited vocabulary, low interest in reading, lack of attention when reading, and minimal reading guidance at school or at home. This study suggests that teachers use varied learning methods and actively involve students to improve reading comprehension skills.